Neurofilament heavy chain and chitinase 3-like 1 as markers for monitoring therapeutic response in multiple sclerosis - Kusnierova, P; Revendova, K Zondra; Karasova, K; Zeman, D; Bunganic, R; Hradilek, P; Volny, O; Ganesh, A; Kovacova, I; Stejskal, D (Multiple sclerosis and related disorders, 2024)
AIMS: The aim of this study was to evaluate the association of serum neurofilament heavy chain (sNfH) and chitinase 3-like 1 (sCHI3L1) with treatment response and disease activity in multiple sclerosis (MS). METHODS: This single-center, prospective, observational cohort study was conducted at the MS Centre, University Hospital Ostrava, Czech Republic, from May 2020 to August 2023. sNfH and sCHI3L1 were determined using ELISA. A mixed-effects linear model with a log-transformed outcome variable was applied. RESULTS: We analyzed 459 samples from 57 people with MS. Patients were sampled an average of 8.05 times during 21.9 months of follow-up. Those experiencing a relapse at sampling had a sNfH concentration 50 % higher than those in remission (exp(β) 1.5, 95 % CI 1.15-1.96). A longer duration of treatment was associated with lower sNfH (exp(β) 0.95, 95 % CI 0.94-0.96). Patients switched from low- to high-efficacy disease-modifying therapies (DMTs) had higher sNfH than patients treated with low-efficacy DMTs only (exp(β) 1.95, 95 % CI 1.35-2.81). Higher sCHI3L1 was associated with older age (exp(β) 1.01, 95 % CI 1.00-1.02) and longer DMT use (exp(β) 1.01, 95 % CI 1.00-1.02). sCHI3L1 values were not associated with relapse at the time of sampling, renal function, sex, or type of DMT. CONCLUSION: In contrast to sCHI3L1, sNfH may be a potential biomarker for monitoring treatment response and confirming clinical relapse in MS. Further research is needed to determine the long-term dynamics of sNfH and develop related treatment strategies.
Keywords: neurofilamentové proteiny; Humans; lidé středního věku; Multiple Sclerosis; hodnocení výsledků zdravotní péče; Neurofilament Proteins; Female; dospělí; ELISA; lidé; Biomarkers; Neurofilament heavy chain; Adult; Multiple sclerosis; imunologické faktory; Follow-Up Studies; ženské pohlaví; protein CHI3L1; biologické markery; roztroušená skleróza; Male; Middle Aged; Chitinase-3-Like Protein 1; Immunologic Factors; mužské pohlaví; prospektivní studie; Chitinase 3-like 1; Outcome Assessment, Health Care; následné studie; Prospective Studies